THE RELATIONSHIP BETWEEN WORKLOAD AND WORK FATIGUE WITH WORK PRODUCTIVITY OF COURIER WORKERS AT PT. NUSANTARA CINTA DAMAI BRANCH - Desi Amanda; Tri Niswati Utami (Journal of Gender and Social Inclusion in Muslim Societies, 2025)
This study used a quantitative design with a cross-sectional design and a total sampling technique on 35 couriers of PT. Nusantara Ekspres, Cinta Damai Branch to analyze the relationship between workload (NASA-TLX) and work fatigue (KAUPK2) with work productivity. The NASA-TLX instrument consists of six dimensions (mental, physical, time pressure, performance, frustration, and effort) with a scale of 0-100 categorized from low to very high. Work fatigue was measured by KAUPK2 (20 items, α = 0.89 in the Indonesian population) and classified into low-high categories. Productivity was measured through a standardized questionnaire and an objective indicator of ≥150 packages/day from the company's internal application data. The Pearson correlation test results showed a positive relationship between workload and productivity (r = 0.442; 95% CI 0.15-0.67; p = 0.008) and a negative relationship between work fatigue and productivity (r = -0.346; 95% CI -0.60 to -0.04; p = 0.042). This analysis indicates an association (not a causal relationship) between workload and fatigue with productivity. Limitations of this study include the small sample size, the data did not consider confounding factors such as age, tenure, route length, weather conditions, and working hours, and the potential for single method bias. Implementation recommendations include scheduling micro-breaks, rotating heavy/light routes, and using NASA-TLX thresholds as indicators of OHS interventions to maintain a balance between workload, fatigue, and productivity.